Assessing and addressing cognitive impairment in bipolar disorder: the International Society for Bipolar Disorders Targeting Cognition Task Force recommendations for clinicians. (18th January 2018) - Miskowiak, KW; Burdick, KE; Martinez‐Aran, A; Bonnin, CM; Bowie, CR; Carvalho, AF; Gallagher, P; Lafer, B; López‐Jaramillo, C; Sumiyoshi, T; McIntyre, RS; Schaffer, A; et al.
Abstract : Objectives: Cognition is a new treatment target to aid functional recovery and enhance quality of life for patients with bipolar disorder. The International Society for Bipolar Disorders (ISBD) Targeting Cognition Task Force aimed to develop consensus‐based clinical recommendations on whether, when and how to assess and address cognitive impairment. Methods: The task force, consisting of 19 international experts from nine countries, discussed the challenges and recommendations in a face‐to‐face meeting, telephone conference call and email exchanges. Consensus‐based recommendations were achieved through these exchanges with no need for formal consensus methods. Results: The identified questions were: (I) Should cognitive screening assessments be routinely conducted in clinical settings? (II) What are the most feasible screening tools? (III) What are the implications if cognitive impairment is detected? (IV) What are the treatment perspectives? Key recommendations are that clinicians: (I) formally screen cognition in partially or fully remitted patients whenever possible, (II) use brief, easy‐to‐administer tools such as the Screen for Cognitive Impairment in Psychiatry and Cognitive Complaints in Bipolar Disorder Rating Assessment, and (III) evaluate the impact of medication and comorbidity, refer patients for comprehensive neuropsychological evaluation when clinically indicated, and encourage patients to build cognitive reserve. Regarding question (IV), there is limited evidence for current evidence‐based treatments but intense research efforts are underway to identify new pharmacological and/or psychological cognition treatments. Conclusions: This task force paper provides the first consensus‐based recommendations for clinicians on whether, when, and how to assess and address cognition, which may aid patients' functional recovery and improve their quality of life.